2007
DOI: 10.5194/acp-7-5775-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total solar eclipse of 29 March 2006 on surface radiation

Abstract: Abstract. Solar irradiance spectral measurements were performed during a total solar eclipse. The spectral effect of the limb darkening to the global, direct irradiance and actinic flux measurements was investigated. This effect leads to wavelength dependent changes in the measured solar spectra showing a much more pronounced decrease in the radiation at the lower wavelengths. Radiative transfer model results were used for the computation of a correction for the total ozone measurements due to the limb darkeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 25 publications
1
40
2
Order By: Relevance
“…This limb darkening is spectrally dependent because radiation from the limb of the solar disk is less intense than that from the centre. Thus the spectral composition of the irradiance of the sun changes during the eclipse (Emde and Mayer, 2007;Kazantzidis et al, 2007;Koepke et al, 2001).…”
Section: Sensitivity Analysis Of the Limb Darkening Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…This limb darkening is spectrally dependent because radiation from the limb of the solar disk is less intense than that from the centre. Thus the spectral composition of the irradiance of the sun changes during the eclipse (Emde and Mayer, 2007;Kazantzidis et al, 2007;Koepke et al, 2001).…”
Section: Sensitivity Analysis Of the Limb Darkening Effectmentioning
confidence: 99%
“…In Kazantzidis (2007), a radiative transfer model was used for computation of a correction for the total ozone measurements due to the limb darkening. This correction was found to be too small (less than 0.01 %) to explain the large decrease in total ozone column.…”
Section: Sensitivity Analysis Of the Limb Darkening Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Zerefos et al [24] pointed out that the eclipse-induced cooling of the ozone layer in the stratosphere is the main source of gravity waves propagating both upwards and downwards. Measurements of total column of ozone [9] using Brever Spectrophotometers have revealed that there was a reduction of 30-40 DU total ozone on the day of eclipse, 29 March 2006, than the day before at Athens. Such a reduction in surface O 3 may be due to decreased efficiency of the photochemical O 3 formation [13].…”
Section: Methodsmentioning
confidence: 99%
“…Several measurements of solar radiation were carried out since 1960; recent works [7,8] focussed on the study of eclipse-induced changes in the spectral solar irradiance at the earth's surface, the effect of multiple scattering on sky brightness, and the wavelength dependence of the limb darkening effect etc.. The radiations in shorter wavelengths (350 nm) are generally influenced more by the eclipse, and at large eclipse percentages (> 85%), it slowly decreases as the eclipse approaches its maximum [9,10] compared to that of the longer wavelengths. Hence, one can expect shorter wavelength radiations during partial eclipse, which is less studied.…”
Section: Introductionmentioning
confidence: 99%